A note on constructing small rotatable designs under first order response surface interference model - Varghese, Eldho; Kumar, Jitendra; Jaggi, Seema; Varghese, Cini; Bhowmik, Arpan (Utilitas Mathematica, 2022)
This paper gives a general methodology for constructing rotatable designs for fitting first order response surface interference model in smaller number of runs. Method given in the paper constructs first order rotatable designs in just 2V runs in comparison to designs with vx2v runs available in literature. The design given in the paper is optimal with respect to the number of level changes. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.